The Herbicide Atrazine Potentiates Angiotensin II-Induced Aldosterone Synthesis and Release From Adrenal Cells - Zimmerman, Arthur D.; Mackay, Laci; Kemppainen, Robert J.; Jones, Melaney A.; Read, Casey C.; Schwartz, Dean; Foradori, Chad D. (Frontiers in Endocrinology, 2021)
Atrazine is one of the most commonly used pre-emergence and early post-emergence herbicides in the world. We have shown previously that atrazine does not directly stimulate the pituitary or adrenal to trigger hormone release but acts centrally to activate a stress-like activation of the hypothalamic-pituitary-adrenal axis. In doing so, atrazine treatment has been shown to cause adrenal morphology changes characteristic of repeated stress. In this study, adrenals from atrazine treated and stressed animals were directly compared after 4 days of atrazine treatment or restraint stress. Both atrazine and stressed animals displayed reduced adrenocortical zona glomerulosa thickness and aldosterone synthase (CYP11B2) expression. To determine if reduced CYP11B2 expression resulted in attenuated aldosterone synthesis, stressed and atrazine treated animals were challenged with angiotensin II (Ang II). As predicted, stressed animals produced less aldosterone when stimulated compared to control animals. However, atrazine treated animals had higher circulating aldosterone concentrations compared to both stressed and control groups. Ang II-induced aldosterone synthesis was also potentiated in atrazine treated a human adrenocortical carcinoma cell line (H295R). Atrazine treated did not alter the expression of the rate limiting steroidogenic StAR protein or angiotensin II receptor 1 in the adrenal. Atrazine treated animals also presented with higher basal blood pressure than vehicle treated control animals suggesting sustained elevations in circulating aldosterone levels. Our results demonstrate that treatment with the widely used herbicide, atrazine, directly increases stimulated production of aldosterone in adrenocortical cells independent of expression changes to rate limiting steroidogenic enzymes.